Analisis Kepuasan Konsumen Pada Pembelian Pupuk Menggunakan Konsep SPK Metode Simple Additive Weigthing - Aras, Mohamad; Persada, Indra Nara; Arpah, M.; Ismail, Riswandhi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
This study aims to measure consumer satisfaction in purchasing puput at CV. Farmer friend. The existence of fertilizer in every area is needed by the community. The growing development of technological knowledge has made many companies compete to establish retailers that can provide good service and needs to consumers. So that there are still many consumers who are still confused about where to buy fertilizer. The problem of this research is the seller's lack of knowledge in determining the criteria for buying fertilizer so that research is needed to determine customer satisfaction, there is fertilizer sales at CV Sahabat Tani. Factors of consumer satisfaction in the purchase of fertilizer seen from product quality, quality of service or services, emotion, price, cost. The Simple Additive Weighting (SAW) method is a method that can be used to find the optimal alternative from a number of alternatives with certain criteria. The SAW concept is simple, easy to understand, and has the ability to measure the relative performance of decision alternatives in a simple mathematical form. The implementation of a consumer decision support system for purchasing fertilizer at CV Sahabat Tani using the Simple Additive Weighting method has provided an alternative ranking of the highest value for purchasing fertilizer that has been recommended by sellers to consumers. By choosing an alternative, customer satisfaction can be used as a decision-making system to increase fertilizer sales and gain the trust of consumers. The lowest value of satisfaction is 0.858 for consumer 1 and the highest value is 1 for consumer V.